WEB-BASED SANTRI MANAGEMENT AND MONITORING SYSTEM INTEGRATED WITH WHATSAPP - Aprillia, Lucita; Agita Rindri, Yang; Agusti Farma, Tri (ITP Press, 2025)
The increasing number of students in Islamic boarding schools (pesantren) has made administrative tasks such as recording student violations, achievements, permissions, and health records more complex. Many schools still manage these data manually, resulting in duplication, delayed communication, and inefficient supervision. This study addresses this issue by developing a Web-Based Santri Management and Monitoring System integrated with WhatsApp, aiming to streamline data management and enhance real-time communication between administrators, guardians, and health staff. The system was developed using the Waterfall methodology, which includes requirement analysis, system design, implementation, testing, and maintenance stages. Three main user roles were defined: administrators, guardians, and health staff, each with specific responsibilities. A User Acceptance Test (UAT) was conducted with 32 respondents, including one administrator, 30 guardians, and one health staff. The results showed satisfaction levels of 100% for administrators, 87% for guardians, and 100% for health staff, indicating high user acceptance. These findings suggest that the system effectively addresses the challenges of manual data management, improves administrative efficiency, and strengthens communication through real-time WhatsApp notifications, providing a comprehensive solution for student monitoring and supervision in Islamic boarding schools.